Interplay of Gender Inequities, Poverty and Caste: Implications for Health of Women in the Cashew Industry of Kerala - C.U. Thresia (Social Medicine Volume 2, No.1, March 2007, 2007)
Despite Kerala's remarkable achievements in the social sector, improvements in quality of life are not distributed uniformly. Exploration of the life of cashew processing women workers indicates high levels of illiteracy, poverty, morbidity, fertility, gender based violence, caste based inequities, and lack of access to health care. To improve the health conditions of women, social and structural factors determining the health of women have to be addressed. Strengthening the public provisions of health and social services is a necessary prerequisite for improving the quality of health care and life. Yet, neoliberal initiatives underway in Kerala State will further endanger the already weakened public health systems.